Preserving linguistic and cultural heritage of the Tuvan ethnos in the digital era - Novikova, Marina L.; Novikov, Filipp N. (The New Research of Tuva, 2024)
This article presents an analysis of effective strategies for preserving and studying the Tuvan language through the application of methods and technologies such as corpus linguistics, artificial intelligence, and crowdsourcing. The paper examines the development process of educational and communicative applications utilizing neural networks, as well as the integration of language community-created projects into national initiatives for preserving and developing the languages of Russia's ethnic groups.The study investigates the digital presence of Tuvan culture and language in generative artificial intelligence systems, including experiments with large language models (GPT-4, Google Gemini, Claude AI) and multimodal technologies, which demonstrated varying levels of representation. The authors also conduct a SWOT analysis of Tuvan linguistic and cultural heritage in the digital age, identifying strengths such as automated material processing and new archival capabilities, as well as weaknesses, threats, and opportunities associated with technological developments and human factors.The primary conclusion, based on positive trends, suggests that combining traditional methods with cutting-edge technologies can play a crucial role in preserving Tuvan language and culture for future generations.
Keywords: Tuvan language; artificial intelligence; machine translation; neural network; language model; digital presence; machine learning